2002
DOI: 10.1203/00006450-200212000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Birth Weight on the Apo E Genetic Determinants of Plasma Lipid Levels in Children

Abstract: To evaluate the influence of birth weight on apolipoprotein (apo) E genetic determinants of plasma lipids levels in prepubertal children we studied 933 healthy children (491 males and 442 females) 6 to 8 years old (mean age of 6.7 y), whose weight was recorded at birth. Plasma lipid and apolipoprotein concentrations and apo E genotypes were determined. We observed a greater effect of the apo E polymorphism on total cholesterol (TC), LDL-cholesterol (LDL-C) and especially apo B levels in children with birth wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 21 publications
(17 reference statements)
2
16
1
Order By: Relevance
“…In our population, we previously described an important influence of apoE genotype on TC, LDL-C, and apoB levels, 18,26 but the results reported here remain without significant changes after correcting by this factor (data not shown). The design of our study cannot address the mechanism by which cholesterol or saturated fat interacts with the polymorphisms.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…In our population, we previously described an important influence of apoE genotype on TC, LDL-C, and apoB levels, 18,26 but the results reported here remain without significant changes after correcting by this factor (data not shown). The design of our study cannot address the mechanism by which cholesterol or saturated fat interacts with the polymorphisms.…”
Section: Discussioncontrasting
confidence: 44%
“…More detailed information about the design of the study is available in previous publications. 18,19 The study protocol complied with Helsinki Declaration guidelines and Spanish legal provisions governing clinical research on humans, and was approved by the Clinical Research Ethics Committee of the Fundació n Jiménez Díaz in Madrid, Spain. Parents were required to sign a written consent for participation of their children in the study.…”
Section: Populationmentioning
confidence: 99%
“…There were no associations between low birth weight and blood lipids in any PPAR-γ2 genotypes. Effect of APOE genotype on total cholesterol, LDL and ApoB has also been reported by others in children with low birth weight [23,24]. The authors suggested that changes in ApoE gene expression may be programmed by in utero nutritional events.…”
Section: Discussionmentioning
confidence: 58%
“…Therefore, it is possible to speculate that increased blood levels of LDL-cholesterol obtained from fat-enriched diets, when available, such as breast-milk, and possibly the enhanced cholesterol absorption from the small intestine (28) likely seen in APOE4 carriers (29), and especially in underweight children (30), would support a rapid developmental catch-up required for optimal development and survival. On the other hand, APOE2 carriers (when not contributing to type III hyperlipidemia) would exhibit lower total cholesterol and LDL-cholesterol levels compared to E3 and E4 bearers (31) and would be at high risk of growth faltering.…”
Section: Discussionmentioning
confidence: 99%